2022
DOI: 10.1002/alz.12831
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4 carrier status and sex differentiate rates of cognitive decline in early‐ and late‐onset Alzheimer's disease

Abstract: Background:We studied the effect of apolipoprotein E (APOE) ε4 status and sex on rates of cognitive decline in early-(EO) and late-(LO) onset Alzheimer's disease (AD). Method:We ran mixed-effects models with longitudinal cognitive measures as dependent variables, and sex, APOE ε4 carrier status, and interaction terms as predictor variables in 998 EOAD and 2562 LOAD participants from the National Alzheimer's Coordinating Center.Results: APOE ε4 carriers showed accelerated cognitive decline relative to non-carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The LOAD group outperformed the EOAD group on Clinical Dementia Rating Scale–Sum of Boxes ( P = 0.0084) and Montreal Cognitive Assessment (MoCA; P = 0.0006) at their initial visit. Of note, some MoCA scores were Mini‐Mental State Examination scores converted using crosswalk analysis ( n = 2992; see Polsinelli et al 8 . for a description of crosswalk data used in these analyses and Powell et al 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The LOAD group outperformed the EOAD group on Clinical Dementia Rating Scale–Sum of Boxes ( P = 0.0084) and Montreal Cognitive Assessment (MoCA; P = 0.0006) at their initial visit. Of note, some MoCA scores were Mini‐Mental State Examination scores converted using crosswalk analysis ( n = 2992; see Polsinelli et al 8 . for a description of crosswalk data used in these analyses and Powell et al 7 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that women who are APOE4 carriers experience faster cognitive decline and amyloid-beta (Aβ) accumulation compared to men with the same genetic makeup (Corder et al 2004 ). This sex–APOE4 genotype interaction significantly influences a range of AD-related outcomes (Christensen et al 2010 ; Altmann et al 2014 ; Kanekiyo et al 2014 ; Tao et al 2018 ; Duarte-Guterman et al 2020 ; Farmer et al 2021 ; Polsinelli et al 2023 ). For instance, males with APOE4 tend to have more cerebral microbleeds, whereas females with the same allele predominantly develop plaques and tangles (Cacciottolo et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The early‐onset AD (EOAD; onset < 65 years) variant is an atypical, insidious, and aggressive form of AD with an accelerated trajectory of cognitive decline and greater pathology burden compared to late‐onset AD (LOAD) 2–5 . EOAD manifests with more extensive neurodegeneration and tau burden in regions classically correlated with AD.…”
Section: Introductionmentioning
confidence: 99%